TrkB is responsible for EMT transition in malignant pleural effusions derived cultures from adenocarcinoma of the lung - Ricci, Alberto (Landes Bioscience, 2013)
Lung cancer is the leading cause of cancer-related mortality worldwide. Recent evidence indicates that tumors contain a subpopulation of cancer stem cells (CSCs) that are responsible for tumor maintenance and spread. CSCs have recently been linked to the occurrence of epithelial-to-mesenchymal transition (EMT). Neurotrophins (NTs) are growth factors that regulate the biology of embryonic stem cells and cancer cells, but still little is known about the role NTs in the progression of lung cancer. In this work, we investigated the role of the NTs and their receptors using as a study system primary cell cultures derived from malignant pleural effusions (MPEs) of patients with adenocarcinoma of the lung. We assessed the expression of NTs and their receptors in MPE-derived adherent cultures vs. spheroids enriched in CSC markers. We observed in spheroids a selectively enhanced expression of TrkB, both at the mRNA and protein levels. Both K252a, a known inhibitor of Trk activity, and a siRNA against TrkB strongly affected spheroid morphology, induced anoikis and decreased spheroid forming efficiency. Treatment with neurotrophins reversed the inhibitory effect of K252a. Importantly, TrkB inhibition caused loss of vimentin expression as well as that of a set of transcription factors known to be linked to EMT. These ex vivo results nicely correlated with an inverse relationship between TrkB and E-cadherin expression measured by immunohistochemistry in a panel of lung adenocarcinoma samples. We conclude that TrkB is involved in full acquisition of EMT in lung cancer, and that its inhibition results in a less aggressive phenotype.